Social Entrepreneurship and Leadership: Creating Impact through Sustainable Business Models - Ahmed Kareem; Noor Shaker (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
This article investigates the intersection of social entrepreneurship and leadership, focusing on how sustainable business models create social and economic impact. Using examples from successful social enterprises, the study highlights the importance of purpose-driven leadership in addressing societal challenges. Findings emphasize the role of collaboration and innovation in achieving scalable solutions.